Perceived mental health, wellbeing and associated factors among Nepali male migrant and non-migrant workers: A qualitative study - Hridaya Raj Devkota; Bishnu Bhandari; Pratik Adhikary (Elsevier, 2021)
Background: Poor mental health and illness among the working population have serious socioeconomic and public health consequences for both the individual and society/country. With a dramatic increase in work migration over the past decades, there is recent concern about the health and wellbeing of migrant workers and their accessibility to healthcare services in destination countries. This study aimed to explore the mental health and wellbeing experiences of Nepali male returnee-migrants and non-migrant workers, and their perceptions about risk factors for poor health and health service accessibility. Methods: This qualitative study was conducted among Nepali migrant and non-migrant workers in February 2020. Four focus group discussions comprising 25 men and a total of 15 in-depth interviews were conducted with male non-migrant and returnee migrant workers from Gulf countries and Malaysia. The discussions and interviews were audio-recorded, transcribed, translated into English and analysed thematically. Result: Migrant workers reported a higher risk of developing adverse mental health conditions than non-migrant workers. In addition, fever, upper respiratory infection, abdominal pain, ulcer, and occupational injuries were common health problems among both migrant and non-migrant workers. Other major illnesses reported by the migrant workers were heat burns and rashes, snake-bites, dengue, malaria, gallstone, kidney failure, and sexually transmitted diseases, while non-migrants reported hypertension, diabetes, and heart diseases. Adverse living and working conditions including exploitation and abuse by employers, lack of privacy and congested accommodation, language barriers, long hours' hard physical work without breaks, and unhealthy lifestyles were the contributing factors to migrant workers' poor mental and physical health. Both migrant and non-migrants reported poor compliance of job conditions and labor protection by their employers such as application of safety measures at work, provision of insurance and healthcare facilities that affected for their wellbeing negatively. Family problems compounded by constant financial burdens and unmet expectations were the most important factors linked with migrant workers' poor mental health. Conclusion: Both migrant and non-migrant workers experienced poor mental and physical health, largely affected by their adverse living and working conditions, unmet familial and financial needs and unhealthy life styles. Greater compliance is needed by employers of work agreements and the promotion of labor rights for worker's health and safety. In addition, policy interventions to raise awareness about occupational health risks and effective safety training for all workers (migrant and non-migrant) are recommended.